Rancang Bangun Alat Monitoring Getaran Dan Suhu Mesin Nirkabel: Perancangan Dan Pembuatan Alat Monitoring Getaran Dan Suhu Mesin Nirkabel - Nugroho, Oktavianus Ardhian; Setiady, Wahyu; Susanto, Joko; Adittya, Evan; Hadiani Wijayanti, Sylvia; Karimayanti, Antonia (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2024)
PT. Tata Metal Lestari (PT. TML) is a company that produces zinc aluminum coated steel and zinc coated steel used for raw materials for mild steel and other construction products. The machine used in the production process of PT. TML uses a lot of large 3-phase AC motorcycles. Because these motors require a very strict maintenance process by measuring and recording the vibration and temperature of the drive motor every day. ATMI Industrial Polytechnic (Polin ATMI) in collaboration with PT. TML jointly developed a tool that aims to collect motorcycle condition data quickly and provide direct warnings to the maintenance team if there are abnormal conditions. The analysis and design method used in this study succeeded in making a vibration and temperature monitoring system tool for non-portable engines that can detect vibration and temperature on the motor using a non-portable network that can be displayed on a screen so that it can help PT. TML. The tool made has a size of 70 x 70 x 40 mm which makes this tool small in size and is designed to be installed in all conditions and positions according to the request of PT. TML, the test results of the vibration value of the prototype have a result of 2% greater while the temperature is 1.5% greater than the value on the measuring instrument.